1990
DOI: 10.1021/bi00484a003
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the major pepsin inhibitor from the intestinal parasitic nematode Ascaris suum

Abstract: The major pepsin inhibitor from Ascaris suum was isolated by affinity chromatography and chromatofocusing. Its amino acid sequence was determined by automated Edman degradation of peptide fragments. Peptides were produced by chemical and enzymatic cleavage of pyridylethylated protein and were purified by reverse-phase high-performance liquid chromatography. The inhibitor consists of 149 residues with the following sequence: QFLFSMSTGP10FICTVKDNQV20FVANLPWTML30EGDDIQVGKE40 FAARVEDCTN50VKHDMAPTCT60KPPPFCGPQD70MK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…An additional orthologue from A. suum was identified by a BLASTp search. The amino acid sequence of this aspartyl protease inhibitor (GenBank P19400 [26]) showed 19% identity to P. tenuis. This ORF was different from both of the A. suum ORFs deduced from ESTs.…”
Section: Resultsmentioning
confidence: 99%
“…An additional orthologue from A. suum was identified by a BLASTp search. The amino acid sequence of this aspartyl protease inhibitor (GenBank P19400 [26]) showed 19% identity to P. tenuis. This ORF was different from both of the A. suum ORFs deduced from ESTs.…”
Section: Resultsmentioning
confidence: 99%
“…(77). Ov-spi-1 and Ov-api-1 genes code for part of a family of proteinase inhibitors originally characterized from Ascaris and which has not been seen outside of the phylum Nematoda (3,51). These inhibitors could support the identification of synthetic molecules to specifically inhibit the endogenous or exogenous corresponding enzymes, and thus interfere with the function of these molecules during development in the host.…”
Section: Resultsmentioning
confidence: 99%
“…The question of selectivity has previously been approached using a peptide inhibitor derived from the round worm Ascaris (27), which was reported to have little or no activity against cathepsin D compared with cathepsin E. However, studies with the naturally occurring inhibitor have been limited by difficulties of purification, and recent analysis has suggested that the recombinant inhibitor may have a slightly different inhibitory profile (28). Follow-up of the initial studies of cathepsin E's role in Ag processing has therefore been limited (29).…”
Section: Discussionmentioning
confidence: 99%